Multiphotonic staging of chronic wounds and evaluation of sterile, optical transparent bacterial nanocellulose covering: A diagnostic window into human skin. Issue 1 (20th June 2018) - Springer, S.; Zieger, M.; Hipler, U. C.; Lademann, J.; Albrecht, V.; Bueckle, R.; Meß, C.; Kaatz, M.; Huck, V.
Abstract: Background: Diagnostics of healing, infection, and inflammation in chronic wounds in comparison with physiological wound healing in acute wounds may help for therapy decisions toward individualized therapy management. With emerging new optical techniques the coupling of optical diagnostic devices with tissue provides a great challenge. Traditional coupling with cover slips is used since the early days of microscopy. In modern health care, hygienic covering of surfaces is necessary to avoid infections and cross‐contaminations. Methods: Measurements in chronic wounds were performed at three different areas including the center of the wound, the border of the wound and healthy skin as comparison area. For each measurement area, three vertical stacks were taken by MPT. Additionally, three different optical measuring procedures (MPT, OCT, CLSM) were used for the examination of BNC foil. Examinations of BNC foil were carried out at two different areas of healthy skin compared to a standard setup as control. Results: The MPT evaluation revealed a distinct difference in the second harmonic generation‐to‐autofluorescence aging index of dermis (SAAID) behavior between the vertical stacks taken at central wound areas and wound margins as well as unaffected skin. Through BNC foil covers, MPT CLSM and OCT images were captured with good quantitative and qualitative results. Conclusions: Phases in chronic wounds could be matched with physiologically healing in acute wounds according to SAAID and MPT imaging. BNC provided an alternative covering for MPT, OCT, and CLSM with clear morphological images.